An Air‐Stable High‐Nickel Cathode with Reinforced Electrochemical Performance Enabled by Convertible Amorphous Li2CO3 Modification - Sheng, Hang; Meng, Xin‐Hai; Xiao, Dong‐Dong; Fan, Min; Chen, Wan‐Ping; Wan, Jing; Tang, Jilin; Zou, Yu‐Gang; Wang, Fuyi; Wen, Rui; Shi, Ji‐Lei; Guo, Yu‐Guo (Advanced materials (Weinheim), 2022)
High‐nickel (Ni ≥ 90%) cathodes with high specific capacity hold great potential for next‐generation lithium‐ion batteries (LIBs). However, their practical application is restricted by the high interfacial reactivity under continuous air erosion and electrolyte assault. Herein, a stable high‐nickel cathode is rationally designed via in situ induction of a dense amorphous Li2CO3 on the particle surface by a preemptive atmosphere control. Among the residual lithium compounds, Li2CO3 is the most thermodynamically stable one, so a dense Li2CO3 coating layer can serve as a physical protection layer to isolate the cathode from contact with moist air. Furthermore, amorphous Li2CO3 can be transformed into a robust F‐rich cathode electrolyte interphase (CEI) during cycling, which reinforces the cathode's interfacial stability and improves the electrochemical performance. The assembled coin cell with this modified cathode delivers a high discharge capacity of 232.4 mAh g–1 with a superior initial Coulombic efficiency (CE) of 95.1%, and considerable capacity retention of 90.4% after 100 cycles. Furthermore, no slurry gelation occurs during the large‐scale electrode fabrication process. This work opens a valuable perspective on the evolution of amorphous Li2CO3 in LIBs and provides guidance on protecting unstable high‐capacity cathodes for energy‐storage devices. A high‐nickel cathode (Ni ≥ 90%) is developed through controlling the surface residual lithium composition with a formed amorphous Li2CO3 protective layer. This cathode can resist corrosion by air, and will be converted into a stable cathode electrolyte interphase during the electrochemical process, resulting in enhanced storage performance and extended cycle life for high‐nickel cathodes.